International Monetary Fund Annual Report 2000 : Making the Global Economy Work for All. (Annual Report of the Executive Board; Annual Report of the Executive Board, 2000)
The Annual Report 2000 to the Board of Governors reviews the IMF's activities, policies, and financial position during the financial year (May 1, 1999 through April 30, 2000), as well as developments in the world economy. The Annual Report 2000 highlights the efforts of the IMF, together with other international institutions and groups, to strengthen the international financial and monetary system, so that future financial crises can be avoided, or better managed. The Report discusses the progress made with transparency and openness on the part of the IMF and its members, with implementing and monitoring the observance bh members of standards and codes of good practice, with helping strengthen members financial systems, with involving the private sector in financial crisis prevention and resolution, and in reforming its lending facilities and policies. The Annual Report also highlights the IMF's greater attention to poverty reduction, giving it a central role in its support for the reform efforts of the poorest countries - ingreater collaboration with the World Bank. Appendixes include an analysis of international reserves changes in fiscal 2000, IMF financial operations and transactions, key policy decisions, IMF relations with othe international organizations, external relations activities, press communiques of key advisory committees, the Executive Board and voting power as of April 30,2000, and changes in membership on the Executive Board. Published in September.